Area Under Curve (AUC) as a Validating Index for the Hypoglyceamic Activity of Sida Acuta Ethanolic Leaf Extract in Experimental Diabetic Animals - Ukpo , Grace; Mbang, Owolabi; Ehianeta , Teddy; Chika, Anyanwu-Ndulewe; Azeez , Ajibola (Nigerian Journal of Pharmaceutical and Applied Science Research, 2020)
Sida acuta, used for treatment of diabetes by traditional healers is evaluated for hypoglyceamic effect of its leaf extract in alloxan-induced diabetes rats relative to metformin and to establish the predictability of Area under the Curve (AUC) as tool for monitoring its hypoglyceamic potential. Diabetic rats with blood glucose levels (BGLs) > 200 mg/dl were screened following 72 hrs post-alloxan induction (150 mg/kg/i.p). The BGLs were determined prior to S. acuta extract and metformin treatments. The extract and metformin were administered daily as follows: group II (induced only); group III (induced + metformin 2.57 mg/kg/p.o); group IV (induced + S. acuta 200 mg/kg/p.o); group V (induced + S. acuta 400 mg/kg/p.o); group VI (induced + metformin + S. acuta 200 mg/kg/p.o) and group VII (induced + metformin + S. acuta 400 mg/kg/p.o). BGLs were observed at 0 hr, 1 hr, 3 hr, 6 hr, 24 hr, 48 hr, 72 hr, 7 days, 14 days and 21 days and AUCs determined from pharmacokinetic plots. Significant decrease in BGLs was observed and AUC trends as IV > III > V > VI > VII establishing an evidence of reduced glucose. Sida acuta (200 mg/kg) showed a better hypoglyceamic property than Metformin